Preparation and characterization of novel addition cured polydimethylsiloxane nanocomposites using nano‐silica sol as reinforcing filler. Issue 12 (21st August 2015) - Chen, Dongzhi; Chen, Fengxiang; Zhang, Hongwei; Yin, Xianze; Liu, Xin; Zhou, Yingshan
Abstract A series of novel addition cured polydimethylsiloxane (PDMS) nanocomposites with various amounts of nano‐silica sol were prepared via hydrosilylation for the first time. The influence of various amounts of nano‐silica sol on the morphology, thermal behavior, mechanical and optical properties of these PDMS nanocomposites was studied in detail. It was found that with an increment in the amount of nano‐silica sol the reinforcing effect of the nano‐silica sol on the thermal and mechanical properties of the PDMS nanocomposites was very noticeable compared with the reference material. The prominent improvements in resistance to thermal degradation and mechanical properties can probably be attributed to the strong interaction of PDMS chains and uniformly dispersed particles resulting from the nano‐silica sol. However, the transparency of the PDMS nanocomposites slightly decreased with an increment in weight fraction of nano‐silica, compared with that of PDMS composite without nano‐silica (Sol‐0), which can probably be ascribed to an increasing size of the aggregated particles in the PDMS nanocomposites. The optimum amount of nano‐silica sol for preparing novel addition curing PDMS nanocomposites was about 15 wt%. © 2015 Society of Chemical Industry